Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-2165
|View full text |Cite
|
Sign up to set email alerts
|

Creak in the Respiratory Cycle

Abstract: Creakiness is a well-known turn-taking cue and has been observed to systematically accompany phrase and turn ends in several languages. In Estonian, creaky voice is frequently used by all speakers without any obvious evidence for its systematic use as a turn-taking cue. Rather, it signals a lack of prominence and is favored by lengthening and later timing in phrases. In this paper, we analyze the occurrence of creak with respect to properties of the respiratory cycle. We show that creak is more likely to accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Increased glottal resistance has also been found in experimental data of natural multiparty conversations (Aare et al 2018). The authors show that creaky voice is more frequent in longer than in shorter exhalation periods, as predicted in the model of Zhang (2016).…”
Section: Laryngeal Compensation For Air Losssupporting
confidence: 57%
“…Increased glottal resistance has also been found in experimental data of natural multiparty conversations (Aare et al 2018). The authors show that creaky voice is more frequent in longer than in shorter exhalation periods, as predicted in the model of Zhang (2016).…”
Section: Laryngeal Compensation For Air Losssupporting
confidence: 57%
“…The measured kinematic output in speech production is, therefore, heavily modulated by the laryngeal configuration and upper vocal tract, which can also compensate for the loss of air. 17,49,50 The control of the larynx and upper articulators may be speaker-specific and could account for the consistency of the cycle shape.…”
Section: Discussionmentioning
confidence: 99%
“…However, results on f0 in fillers, across languages and age, are mixed, possibly because authors have not analyzed the data based on prosodic context. Generally, we might predict that utterance-final positions have lower f0 as a function of declination (e.g., Gendrot and Schmid 2011) and utterance-final use of creaky phonation (Aare et al 2018;Ogden 2001). Zhang (2016b) has also suggested that speakers may make glottal adjustments to conserve airflow reserves under some conditions (e.g., long utterances), such as adopting more adducted laryngeal postures.…”
Section: Research Questions and Predictionsmentioning
confidence: 99%